Laboratory Risk Assessment of Three Entomopathogenic Fungi Used for Pest Control toward Social Bee Pollinators - Leite, Mariana O. G.; Alves, Denise A.; Lecocq, Antoine; Malaquias, José Bruno [UNESP]; Delalibera, Italo; Jensen, Annette B. (MDPI, 2022)
The use of fungal-based biopesticides to reduce pest damage and protect crop quality is often considered a low-risk control strategy. Nevertheless, risk assessment of mycopesticides is still needed since pests and beneficial insects, such as pollinators, co-exist in the same agroecosystem where mass use of this strategy occurs. In this context, we evaluated the effect of five concentrations of three commercial entomopathogenic fungi, Beauveria bassiana, Metarhizium anisopliae, and Cordyceps fumosorosea, by direct contact and ingestion, on the tropical stingless bees Scaptotrigona depilis and Tetragonisca angustula, temperate bee species, the honey bee Apis mellifera, and the bumble bee Bombus terrestris, at the individual level. Furthermore, we studied the potential of two infection routes, either by direct contact or ingestion. In general, all three fungi caused considerable mortalities in the four bee species, which differed in their response to the different fungal species. Scaptotrigona depilis and B. terrestris were more susceptible to B. bassiana than the other fungi when exposed topically, and B. terrestris and A. mellifera were more susceptible to M. anisopliae when exposed orally. Interestingly, increased positive concentration responses were not observed for all fungal species and application methods. For example, B. terrestris mortalities were similar at the lowest and highest fungal concentrations for both exposure methods. This study demonstrates that under laboratory conditions, the three fungal species can potentially reduce the survival of social bees at the individual level. However, further colony and field studies are needed to elucidate the susceptibility of these fungi towards social bees to fully assess the ecological risks.
Keywords: biopesticides; bumble bees; honey bees; stingless bees; toxicology